2007
DOI: 10.1007/s00167-007-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the Autologous Quadriceps Tendon (BQT) and the Autologous Patella Tendon (BPTB) for the reconstruction of the Anterior Cruciate Ligament

Abstract: The use of the BPTB-autograft is a very common method for ACL reconstruction. Nevertheless, the problem of the typical donor-site-morbidity is unresolved. Recently, a transplant of quadriceps tendon, with an attached bone block (BQT) has been increasingly relied upon. The purpose of this study was to examine the clinical results of a group of patients after arthroscopic ACL reconstruction using either BPTB or quadriceps tendon autograft after a minimum follow-up of 2 years in terms of knee joint stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 26 publications
4
82
3
7
Order By: Relevance
“…Many studies reported that the ACL reconstruction with BPTB autograft produced good clinical results (Harner et al, 1996;Fu et al, 2000;Deehan et al, 2000;Gorschewsky et al, 2007;Han et al, 2008). However, a desire to avoid the sacrifice of autologous tissue and to minimize surgical trauma and postoperative donor site morbidity has promoted the consideration of alternative graft sources (Stringham et al, 1996;Siebold et al, 2003;Barrett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that the ACL reconstruction with BPTB autograft produced good clinical results (Harner et al, 1996;Fu et al, 2000;Deehan et al, 2000;Gorschewsky et al, 2007;Han et al, 2008). However, a desire to avoid the sacrifice of autologous tissue and to minimize surgical trauma and postoperative donor site morbidity has promoted the consideration of alternative graft sources (Stringham et al, 1996;Siebold et al, 2003;Barrett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been retrospective studies that compared QTPB and BPTB morbidities following ACLR. 13,14 The outcomes of these studies demonstrated similar graft failure rates, 13,14 and similar flexion/extension deficits. 13 However, increased anterior knee pain and donor site morbidity was greater for individuals who underwent BPTB compared with the QTPB group.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 67%
“…However, two retrospective studies that were not included in the CAT compared subjective patient-reported outcomes between BPTB and QTPB patients. 13 The results indicated no significant differences in Lysholm scores when compared postoperatively (BPTB = 92.8, QTBP = 91.5 13 ; BPTB = 95, QTBP = 94 14 ). Additional clinician-based outcomes were also measured in each of the studies, including laxity/ anteroposterior translation, [3][4][5][6] knee function using ROM 3,6 and one-leg hop index, 3 patellofemoral crepitus, 3 thigh girth, 4 muscle strength, 4,6 joint space narrowing, 4 anterior knee pain, 6 and the IKDC guidelines were used during physical examination.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 88%
“…Pre-operative knowledge of graft size will allow surgeons greater confidence in evaluating and counseling patients regarding graft choice. Consequently, alternative options of choosing another graft source can then be considered prior to 19,20 . The reported benefits of using the QT are that it eliminates the morbidities related to other graft options, with less reported anterior knee pain and numbness compared with PT-bone graft, as well as none of the residual cramping that can occur with hamstring tendon harvest.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%